Students’ and Teachers’ Attitudes toward Using Audiovisual Chat in Teaching English ‎Language Skills and Areas to the Seventh Grade Students - Mayyas ‎, Hazim; AbuSeileek, Ali (Jordan Journal of Educational Sciences, 2023)
The current study aimed to investigate students’ and teachers’ attitudes toward using the audiovisual chat method in teaching English language skills (listening, speaking, reading, and writing) and areas (grammar, vocabulary and pronunciation) to 7th grade students. To achieve the goals of the study, a descriptive research design was adopted using the quantitative method. The data were collected through a questionnaire distributed to 32 male students from Al-Buweideh Secondary Comprehensive School for Boys at Ramtha during the second semester of the academic year 2021-2022, and another questionnaire was directed to 16 teachers from Ramtha public schools. The results of the study revealed that the general attitudes of students and teachers toward using the audiovisual chat method are positive. In accordance with these results, a set of recommendations was suggested for the Ministry of Education, curriculum designers, and EFL researchers and teachers